Highway 54 the design and development of a 3D multiplayer game - Bonayon, Roel (2002)
Highway 54 is a third person driving simulation game. The game features the Philippine Jeepney and is set in a fully 3-dimensional futuristic Manila. The object of the game is to earn points by servicing passengers. The Highway 54 project is a MOD development - a Quake 3 Engine Modification. The Quake 3 engine was chosen for Highway 54 because it is a very flexible and modularized tool. The game development involved the design and construction of maps and the modeling of jeepneys. The game physics, particularly vehicle dynamics, is implemented through variations in the code. Highway 54 allows support for multiplayer gaming over a local area network or the internet. This capacility appeals to the Filipino network gaming community.